Research on Key Technology and Application of Airborne Wireless Systems for Public Mobile Communication - Miao Yang; Xing Pu; Huiling Dai (Dianxin kexue)
The technologies and features of airborne wireless systems for public mobile communication were analyzed, applications in different states were compared. At last, the issues that need attention were indicated that frequency assignment and radio station using must coexist with other airborne systems, which could influence the safety of the aircraft.